Verbs of movement in figurative meaning - Mohammed, Iman Owaid (Al-Adab Journal, 2019)
The article describes the semantic flexibility inherent in the verbs of movement, which allows you to in detail and fully cover with lexical means the entire sphere of extra-linguistic reality related to the processes of movement. The variation of values resulting from the appearance of new differential features is represented; changes in the ratio of the semantic significance of various features of one lexico-semantic variant changes in the sphere of reality – an object that moves or is experiencing movement itself under the influence of extraneous forces; expansion of meaning that allows nominating other areas of reality; generalization of the meaning of verbs to the extent that it becomes universal, having lost connection with any particular type of movement, type of environment or method of movement; phraseological transfer of values. It is argued that these semantic phenomena cause a process of secondary nominations, the emergence of nominative-derived verbs.